Fault-tolerant and QoS based Network Layer for Security Management - Kais Mekki; Ahmed Zouinkhi; Mohamed Naceur Abdelkrim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Wireless sensor networks have profound effects on many application fields like security management which need an immediate, fast and energy efficient route. In this paper, we define a fault-tolerant and QoS based network layer for security management of chemical products warehouse which can be classified as real-time and mission critical application. This application generate routine data packets and alert packets caused by unusual events which need a high reliability, short end to end delay and low packet loss rate constraints. After each node compute his hop count and build his neighbors table in the initialization phase, packets can be routed to the sink. We use FELGossiping protocol for routine data packets and node-disjoint multipath routing protocol for alert packets. Furthermore, we utilize the information gathering phase of FELGossiping to update the neighbors table and detect the failed nodes, and we adapt the network topology changes by rerun the initialization phase when chemical units were added or removed from the warehouse. Analysis shows that the network layer is energy efficient and can meet the QoS constraints of unusual events packets.